Défis, la galerie VEGA en Wallonie. - Charlier, Jacques; Corillon, Patrick; Repriels, Manette; Galerie Véga, Bruxelles; Centre d'Art Contemporain, Bruxelles (Bruxelles : Galerie Vega Bruxelles, 2001)
Becher, Bernd & Hilla ; Beuys, Joseph ; Bochner, Mel ; Broodthaers, Marcel ; Bury, Pol ; Cadere, Andre ; Charlier, Jacques ; Corillon, Patrick ; Delahaut, Jo ; Denée, Michel ; Downsbrough, Peter ; Gasparotto, Paolo ; Gilbert & George ; Graham, Dan ; Hantaï, Simon ; Houcmant, Pierre ; Joosen, Nic ; Klenes, Anne-Marie ; Kozakis, Nicolas ; Croix, Roger La ; Leisgen, Barbara & Michael ; LeWitt, Sol ; Nyst, Jacques-Louis ; Oppenheim, Dennis ; Panamarenko ; Titus-Carmel, Gérard ; Tulumello, Agostino ; Wuidar, Leon
Frans
Défis, la galerie VEGA en Wallonie, Centre d'Art Contemporain Bruxelles, 20.09 - 27.10.2001
boek